2021
DOI: 10.1371/journal.pntd.0009488
|View full text |Cite
|
Sign up to set email alerts
|

The synthetic synergistic cinnamon oil CIN-102 is active against Madurella mycetomatis, the most common causative agent of mycetoma

Abstract: Mycetoma is a devastating neglected tropical infection of the subcutaneous tissue and most commonly caused by the fungus Madurella mycetomatis. Treatment of mycetoma consists of a combination of a long term antifungal treatment with itraconazole and surgery. However, treatment is associated with low success rates. Therefore, there is a need to identify novel treatments for mycetoma. CIN-102 is a synthetic partial copy of cinnamon oils with activity against many pathogenic bacteria and fungi. In this study we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In the past, mammalian models have been used for grain formation, but in 2015 we demonstrated that grain formation can occur in the M. mycetomatis infected invertebrate G. mellonella [22,23]. In previous studies as well in this study, we used this G. mellonella grain model to determine if the compounds active against hyphae in vitro can penetrate grains in vivo [10,[22][23][24]. Four compounds, ravuconazole, olorofim, fenbendazole and MMV1782387 were able to significantly prolong larvae survival on day ten.…”
Section: Discussionmentioning
confidence: 89%
“…In the past, mammalian models have been used for grain formation, but in 2015 we demonstrated that grain formation can occur in the M. mycetomatis infected invertebrate G. mellonella [22,23]. In previous studies as well in this study, we used this G. mellonella grain model to determine if the compounds active against hyphae in vitro can penetrate grains in vivo [10,[22][23][24]. Four compounds, ravuconazole, olorofim, fenbendazole and MMV1782387 were able to significantly prolong larvae survival on day ten.…”
Section: Discussionmentioning
confidence: 89%
“…The MM55 isolate, which is resistant to cinnamaldehyde (minimal inhibitory concentration/MIC = 222 μg/mL), was used for this study. [14] Although none of the compounds did completely inhibit fungal growth at concentrations of 25 μM and 100 μM, some reduction in growth was observed compared to the solvent-treated control. Compound 4 c demonstrated the highest in vitro activity with percentages metabolic activity of 44.1 % and 26.6 %, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…Natural products from plants are a rich source for the identification and development of new drugs against human infectious diseases caused by protozoa and fungi. [11][12][13][14] Natural ingredients of several Piper plants exhibited promising activities against various pathogenic protozoal parasites such as Leishmania. The amide alkaloids piperine, isolated from black pepper (Piper nigrum), and piperlongumine (also called piplartine), isolated from long pepper (Piper longum) and other Piper species, are prominent examples of antileishmanial compounds from these plants.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations